Short- and Long-Term Effects on Knowledge, Skills, and Attitudes About a Sonography Training Concept for Medical Students. (January 2020) - Vennemann, Sabrina; Holzmann-Littig, Christopher; Marten-Mittag, Birgitt; Vo Cong, Minh; Berberat, Pascal; Stock, Konrad
Objectives: Worldwide medical schools that provide sonography training appear to be very heterogeneous in their offerings. A medical school has developed a training program with limited resources, which used a peer teaching method, to provide sonography training. The implemented courses consist of a voluntary laboratory practical and a required didactic seminar. Methods: To analyze this concept, the effects on knowledge, skills, and attitudes were examined by using surveys, multiple-choice tests, and practical tests. Results: The teaching concept demonstrated a positive effect on theoretical knowledge, practical skills, and attitudes. Nevertheless, some practical skills such as conducting gallbladder sonography deteriorated over the time of the study. Discussion: The peer-teaching approach with well-trained students as instructors and tutorials in smaller groups appeared to be a key element for success. This cohort study underlines the need to provide both theoretical and practical mandatory training. Conclusion: Peer teaching may be a cost-effective way to teach sonography skills to medical students during their training.